Skin lesions due to human bite. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 3-year-old little girl was first observed for pyoderma of the lower limbs. During the physical examination we accidentally noticed asymptomatic lesions of the left cheek and right upper limb. The dermatological examination showed two linear lesions arranged at an acute angle on the cheek (Fig. 1), the upper erythematous and the lower eroded and half a millimeter deep. On the right upper limb (Fig 2) we observed three groups of hypochromic lesions, the first on the arm, the second on the elbow and the third on the forearm. The lesions were hypochromic, grouped in two or three elements, had linear or triangular form and typically were separated by healthy skin. In a supplement of history, the mother informed us that all the lesions of the cheek and upper limb were the result of bites of the 1-year-old brother.